(3GdcGaj aj Ydei GdYQhV hGdbhGais - (3TgGH GdOjf CHh GdYHGS CMeO Hf YHGO Hf TYjH GdUGHi GdbGgQi GdTGaYjs; (3TgGH GdOjf CHh GdYHGS CMeO Hf YHGO Hf TYjH GdUCHj GdbGgQj GdTGaYj, GdNhGU,J (B858 (3g` s ((3eQJVi Hf eUWai Hf MSf GdcQOi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO agPG JCdja cGai ai Ydei GdYQhV hGdbhGai hGddg Gdehab hYdjg GdJhcd GdChd ajg ebOeI hHGHkG hNGJeI s
(3BNQgG (B:s
(3hgPG BNQ eG CQOfG LeYg , hddg GdMeO ChdkG hBNQkG SQkG hYdGfjI Je HMeO Gddg hYhfg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B259 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B131s
Keywords: (3GdYQhV hGdbhGais